THE EFFECT OF USING SOCIAL MEDIA TOWARDS STUDENTS’ READING COMPREHENSION - Prima Gusti Yanti; Fairul Zabadi; Fauzi Rahman (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to determine the effect of the activity of using social media on the ability of college students to reading comprehension. This type of research is quantitative with a correlational method. The sample in this study was taken with simple random sampling. PBSI FKIP UHAMKA active students approximately 600 students who if taken a sample of 25% at random, would choose 150 students. Data collection techniques using questionnaires and reading tests, while data analysis using descriptive statistics and simple linear regression equations. The results of this study indicate that the intensity of the use of social media in the percentage of students is 45% moderate, 25% low, 25% high, and 7% very high, obtained the regression equation . These findings indicate that the more activity on social media, the lower the level of reading comprehension although not significantly.